2014
DOI: 10.1002/env.2284
|View full text |Cite
|
Sign up to set email alerts
|

Spatial sampling on streams: principles for inference on aquatic networks

Abstract: For ecological and environmental data, prior inquiries into spatial sampling designs have considered two-dimensional domains and have shown that design optimality depends on the characteristics of the target spatial domain and intended inference. The structure and water-driven continuity of streams prompted the development of spatial autocovariance models for stream networks. The unique properties of stream networks, and their spatial processes, warrant evaluation of sampling design characteristics in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Som et al . () found that a spatially balanced survey design, similar to the one used here, provides reasonably accurate parameter estimates for the predictors and the tail‐up covariance structure. Our leave‐one‐out cross‐validation analysis also indicates reasonable model fits and predictive abilities (Table ).…”
Section: Discussionmentioning
confidence: 61%
“…Som et al . () found that a spatially balanced survey design, similar to the one used here, provides reasonably accurate parameter estimates for the predictors and the tail‐up covariance structure. Our leave‐one‐out cross‐validation analysis also indicates reasonable model fits and predictive abilities (Table ).…”
Section: Discussionmentioning
confidence: 61%
“…Each of our 19 streams flows directly into a single lake-river network independently of each other. This simple network is similar to coastal streams that drain directly into the ocean but differ from more complex stream networks that are spatially correlated due to convergence downstream (Peterson et al 2013;Som et al 2014). Therefore, temperature for a downstream site is a function of upstream tributaries in addition to watershed characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…This directional autocorrelation could be useful for informing the selection of cost-effective sites because downstream sites integrate upstream temperatures. Som et al (2014) provide suggestions for the most effective sampling designs for monitoring stream networks. This framework could be easily modified to integrate the autocorrelation between connected sites and which may provide additional cost savings due to higher correlations Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Along with increasingly available spatial data coverages and a push for more spatially explicit modeling in watersheds, more and more observed response data from a broad range of monitoring programs are also becoming available. The response data can come from existing monitoring programs (Peterson et al ., ; Isaak et al ., ) or studies specifically designed for SSN modeling (Frieden et al ., ; Som et al ., ). Because of the spatial dependencies among monitoring sites inherently necessary for SSN modeling, the sampling design of such studies influences the statistical analysis approaches that can be adopted (McDonnell et al ., ) and possibly the validity of the inferences made from their results.…”
Section: Introductionmentioning
confidence: 97%